Sustainability Reporting in the Mining Sector: Exploring Its Symbolic Nature - Böhling, Kathrin (2017)
Sustainability reporting (SR) has become a well-entrenched practice in themining sector. Failure to adequately live up to societal expectations is nowconsidered a significant threat to the viability of the industry. There is generalagreement that broad endorsement of standards for nonfinancial disclosuresupports mining companies to improve their image, while conflicts persist.Because sustainability reports ?speak? on behalf of sustainably operatingorganizations and may create socio-political effects, we explore the symbolicnature of SR. We conceive of SR as a performative practice to researchhow it interferes with the world that it seeks to represent. Our case studyresearch suggests that conformity with global templates is not an end in itselfbut might create below-compliance effects if a common interest in mining isdeveloped in local arenas that avoids clarification of impacts and maintainsambiguity over responsibility.